Stryphnodendron adstringens have a modulatory effect on inflammatory cytokines markers of in vitro activated macrophages - Ivana Beatrice Mânica da Cruz; Cibele Ferreira Teixeira; Neida Luiza Pellenz; Moisés Henrique Mastella; Verônica Farina Azzolin; Euler Esteves Ribeiro; Fernanda Barbisan (Exploration of Drug Science)
Aim: The purpose of this study is to conduct a comprehensive investigation into the modulatory effects of Stryphnodendron adstringens (Mart.; S. adstringens), a Brazilian wound-healing plant, on the expression of inflammatory cytokines. This will be achieved using an in vitro protocol with the commercial macrophage cell line RAW 264.7. Methods: The macrophage inflammatory response was induced by the natural antigen phytohemagglutinin (PHA), with and without supplementation of different concentrations of S. adstringens extract. The effects on cell proliferation rate and the concentration and production of transcripts of pro-inflammatory cytokines interleukin 1β (IL-1β), IL-6, tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ), as well as the anti-inflammatory cytokine IL-10, were assessed using spectrophotometric, immunoassay, and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) techniques. Results: S. adstringens extract at all concentrations tested here reduced the cellular proliferation rate of activated macrophages. Extracts at concentrations of 0.49 mg/mL and 0.99 mg/mL decreased the protein and gene expression of pro-inflammatory cytokines, exhibiting the opposite effect concerning IL-10. Conclusions: The findings suggest that the wound-healing action of S. adstringens may encompass differential modulation of inflammation associated with tissue injury.